Magnetic resonance imaging as a diagnostic tool for periodontal disease: A prospective study with correlation to standard clinical findings—Is there added value?. (3rd May 2021) - Probst, Monika; Burian, Egon; Robl, Teresa; Weidlich, Dominik; Karampinos, Dimitrios; Brunner, Teresa; Zimmer, Claus; Probst, Florian Andreas; Folwaczny, Matthias
Abstract: Aim: To evaluate the correlation between standard clinical findings, radiographic (OPT) and magnetic resonance imaging (MRI) as well as to assess whether MRI is capable of providing additional information related to the severity and extent of periodontal disease. Methods: 42 patients with generalized periodontitis received pre‐interventional MRI scans. These were compared to MR images of a periodontal healthy control group ( n  = 34). The extent of the osseous oedema, detected by MRI, was set in correlation with clinical periodontitis‐associated findings. Results: A highly significant correlation between bone oedema and clinical testings such as probing depth ( p  < 0.0001) and bleeding on probing ( p  < 0.0001) was revealed. The oedema exceeded the extent of demineralized bone. Patients with a positive BOP test showed a 2.51‐fold increase in risk of already having a bone oedema around the respective tooth even if probing depth was ≤3 mm (logistic binary regression analysis, OR 2.51; 95% CI: 1.54–4.11; p  < 0.0001). Conclusion: MRI findings correlated with standard clinical findings, and MRI was able to depict intraosseous changes before any osseous defect had occurred.